Commoning mobility: Towards a new politics of mobility transitions. Issue 2 (5th February 2019) - Nikolaeva, Anna; Adey, Peter; Cresswell, Tim; Lee, Jane Yeonjae; Nóvoa, Andre; Temenos, Cristina
Abstract : Scholars have argued that transitions to more sustainable and just mobilities require moving beyond technocentrism to rethink the very meaning of mobility in cities, communities, and societies. This paper demonstrates that such rethinking is inherently political. In particular, we focus on recent theorisations of commoning practices that have gained traction in geographic literatures. Drawing on our global comparative research of low‐carbon mobility transitions, we argue that critical mobilities scholars can rethink and expand the understanding of mobility through engagement with commons–enclosure thinking. We present a new concept, "commoning mobility, " a theorisation that both envisions and shapes practices that develop fairer and greener mobilities and more inclusive, collaboratively governed societies. Our analysis introduces three "logics" of mobility transition projects. First, the paper discusses how a logic of scarcity has been a driver for mobility planning as the scarcity of oil, finance, space, and time are invoked across the world as stimuli for aspiring to greener, "smarter, " and cheaper mobilities. The paper then identifies two responses to the logic of scarcity: the logics of austerity and the logics of commoning. Austere mobilities are examined to problematise the distribution of responsibility for emissions and ensuing injustices and exclusion in low‐carbon transitions. The logics of commoning shows a potential to reassess mobility not only as an individual freedom but also as a collective good, paving the way for fairer mobility transitions and a collaborative tackling of sustainable mobility challenges. Abstract : Drawing on a global comparative research of low‐carbon mobility transitions, the paper criticises the logics of scarcity that are ubiquitous in debates surrounding mobility and society in the 21st century. It discusses two responses to such logics: austere mobilities and commoning mobility. Austere mobilities are examined to problematise the distribution of responsibility for emissions and ensuing injustices and exclusion in low‐carbon transitions. Rethinking mobility as a commons shows a potential to reassess mobility not only as an individual freedom but as a collective good, paving the way for fairer mobility transitions and a collaborative tackling of sustainable mobility challenges.